The effect of gut microbiome-targeted therapies in nonalcoholic fatty liver disease: a systematic review and network meta-analysis - Song, Yijia; Liu, Sutong; Zhang, Lihui; Zhao, Wenxia; Qin, Yuanmei; Liu, Minghao (Frontiers in Nutrition, 2025)
BackgroundThe incidence of NAFLD is increasing. Preclinical evidences indicate that modulation of the gut microbiome could be a promising target in nonalcoholic fatty liver disease.MethodA systematic review and network meta-analysis was conducted to compare the effect of probiotics, synbiotics, prebiotics, fecal microbiota transplant, and antibiotics on the liver-enzyme, metabolic effects and liver-specific in patients with NAFLD. The randomized controlled trails (RCTs), limited to English language were searched from database such as Pubmed, Embase, Web of science and Cochrane Library from inception to November 2024. Review Manager 5.3 was used to to draw a Cochrane bias risk. Inconsistency test and publication-bias were assessed by Stata 14.0. Random effect model was used to assemble direct and indirect evidences. The effects of the intervention were presented as mean differences with 95% confidence interval.ResultsA total of 1921 patients from 37 RCTs were eventually included in our study. 23 RCTs evaluated probiotics, 10 RCTs evaluated synbiotics, 4 RCTs evaluated prebiotics, 3 RCTs evaluated FMT and one RCT evaluated antibiotics. Probiotics and synbiotics were associated with a significantly reduction in alanine aminotransferase [ALT, (MD: −5.09; 95%CI: −9.79, −0.39), (MD: −7.38, 95CI%: −11.94, −2.82)] and liver stiffness measurement by elastograph [LSM, (MD: −0.37;95%CI: −0.49, −0.25), (MD: −1.00;95%CI: −1.59, −0.41)]. In addition to, synbiotics was superior to probiotics in reducing LSM. Synbiotics was associated with a significant reduction of Controlled Attenuation Parameter [CAP, (MD: −39.34; 95%CI: −74.73, −3.95)]. Both probiotics and synbiotics were associated with a significant reduction of aspartate transaminase [AST, (MD: −7.81; 95%CI: −15.49, −0.12), (MD: −13.32; 95%CI: −23, −3.64)]. Probiotics and Allogenic FMT was associated with a significant reduction of Homeostatic Model Assessment for Insulin Resistance [HOMA-IR, (MD: −0.7, 95%CI: −1.26, −0.15), (MD: −1.8, 95%CI: −3.53, − 0.07)]. Probiotics was associated with a significant reduction of body mass index [BMI, MD: −1.84, 95%CI: −3.35, −0.33].ConclusionThe supplement of synbiotics and probiotics maybe a promising way to improve liver-enzyme, LSM, and steatosis in patients with NAFLD. More randomized controlled trials are needed to determine the efficacy of FMT and antibiotics on NAFLD. And the incidence of adverse events of MTTs should be further explored.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, CRD42023450093.